Une nouvelle génération féministe au sein de l’islam traditionaliste : Une exception indonésienne ? - Andrée Feillard; Pieternella van Doorn-Harder (Revue des Mondes Musulmans et de la Méditerranée)
Militantism in favor of women’s rights is about one century old., but the fall of President Soeharto in 1998 has accelerated an intense competition between Muslim activists, divided between those in favor of Islamic Law, and those firmly opposed to it. This article discusses the challenges this development has created for Indonesian Muslim feminists, especially those belonging to the traditionalist organization of the Nahdlatul Ulama (NU). Aiming at nation-wide introduction of the Shari’a law, Islamists’ discourses target women’s morality, bodies, and public positions. Symbols of these political and ideological battles are, among others, a recent law against pornography that regulates the interpretation of decency at a national level, and national campaigns promoting polygamy, a practice which the majority of Indonesian Muslims consider to be undesirable.To support their advocacy for women’s basic human and religious rights, these Muslim feminists have created counter discourses based on vigorous Qur’an interpretations. Deeply rooted in Islamic knowledge and being connected to a wide network of Islamic education, they represent a unique, indigenous form of Islamic feminism defending their own cause, no longer that of the men.We argue that this pivotal role played in Indonesia by feminists of Traditionalist Islam is partly due to the low profile of secular feminists who have been intimidated by special historical circumstances, the suppression of the left in 1965 and the derogatory discourse concerning Muslims with Hindu-Buddhist background in Java, delegitimized as belonging to the “abangan” category. However, this Muslim feminism has triggered a conservative reaction which seems to have grown in strength after the death December 30, 2009, of Abdurrahman Wahid, one of the most audacious supporters.